Inovasi Kue Putri Salju Menggunakan Tepung Mocaf sebagai Alternatif Pengganti Tepung Terigu dalam Pembuatan Kue - Aisha Salsabilla; Ita Fatkhur Romadhoni (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Putri salju is a popular Indonesian cookie traditionally served at various events. It is typically made from wheat flour, powdered sugar, egg yolks, peanuts, cashews, fat, and milk powder. In this research, putri salju was innovated by using mocaf flour as a substitute for wheat flour. The aim of this research is to determine: 1) the potential of mocaf flour as a substitute for wheat flour through organoleptic tests; 2) the best formula for substituting mocaf flour with wheat flour; and 3) the nutritional content of putri salju made with mocaf flour. The research method used is an experimental approach, which involved testing on 30 respondents, and the data were analyzed using one-way ANOVA in the SPSS program. Nutritional content was tested through chemical analysis in the laboratory. The results of this research are as follows: 1) The characteristics of the putri salju are light yellow, neatly crescent-shaped, free from the mocaf aroma, with a sweet and savory taste, crispy texture, and fine crumbs. 2) The average score for organoleptic tests was 3.41, with criteria such as light yellow color, neatly shaped crescent, no mocaf aroma, sweet and savory taste, moderately crispy texture, and fine crumb. 3) Based on laboratory tests, every 100 grams of putri salju contains 365.30 kcal, with 66.80% carbohydrates, 8.71% protein, 7.08% fat, and 3.02% moisture. These findings indicate that mocaf flour can be a viable substitute for wheat flour in making putri salju without compromising the taste, texture, or nutritional quality, making it a suitable option for consumers seeking gluten-free alternatives while maintaining the authenticity of this traditional snack.